Amyloid Diseases 2019
DOI: 10.5772/intechopen.84238
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Function of Non-Proteolytic Amyloid-β Chaperones in Alzheimer’s Disease

Abstract: This chapter attempts to explore protective role of chaperone proteins in the neurodegenerative diseases caused by amyloidosis. These chaperones prevent amyloid pathology either directly, through chemical interactions with amyloidogenic species to mediate their refolding, solubilization and degradation, or indirectly, by scavenging reactive oxygen species produced as by-products of amyloid aggregation. Here we focus on structural and morphological changes during aggregation of amyloids which have been identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2
2
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 101 publications
0
7
0
Order By: Relevance
“…In addition to having direct effects of GBP on Aβ, other possibilities could also explain its protective effects. For example, a potential interaction with chaperones could affect folding and assembly of proteins, 42,43 and the degradation of misfolded proteins, preventing their toxic effects. 44 Heat shock proteins, for example, were reported to prevent Aβ 40 and Aβ 42 aggregation and unfold misfolded oligomers.…”
Section: ■ Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to having direct effects of GBP on Aβ, other possibilities could also explain its protective effects. For example, a potential interaction with chaperones could affect folding and assembly of proteins, 42,43 and the degradation of misfolded proteins, preventing their toxic effects. 44 Heat shock proteins, for example, were reported to prevent Aβ 40 and Aβ 42 aggregation and unfold misfolded oligomers.…”
Section: ■ Resultsmentioning
confidence: 99%
“…In addition to having direct effects of GBP on Aβ, other possibilities could also explain its protective effects. For example, a potential interaction with chaperones could affect folding and assembly of proteins, , and the degradation of misfolded proteins, preventing their toxic effects . Heat shock proteins, for example, were reported to prevent Aβ 40 and Aβ 42 aggregation and unfold misfolded oligomers. A recent study showed that a mutant form of the Bri2 BRICHOS chaperone was able to block the aggregation of Aβ 42 into toxic species, , suggesting that the potentiation of endogenous chaperones could reduce the neuro­toxic effects of the Aβ peptide.…”
Section: Discussionmentioning
confidence: 99%
“…of axonal injury are potential avenues which can be explored for AD theranostics [47]. Our results pave the way for the study of other endogenous proteins with significant potential as a chaperone for aggregation-prone amyloids [48]. This work highlights the importance of the use of modifiable contrast agents with engineered coatings to enhance detection of properties of biocompatible diagnostic probes.…”
Section: Discussionmentioning
confidence: 79%
“…The antibodies and synthetic molecules have an inherent risk of triggering immunogenic reactions in the body. Many non-proteolytic proteins, such as Lipocalin-type Prostaglandin D Synthase (L-PGDS), clusterin, αB-crystallin, and α2-Macroglobulin, act as extracellular chaperones and can inhibit the aggregation of Aβ [34,35]. These endogenous human proteins act as chaperones for misfolded Aβ peptides and show disaggregase activity towards the insoluble Aβ aggregates by breaking them down into monomers.…”
Section: Magnetic Resonance Imaging Probes For Alzheimer's Disease Thmentioning
confidence: 99%